CHEMICAL AND PHYSICAL ATTRIBUTES OF AN OXISOL AT DIFFERENT CROP LIVESTOCK SYSTEMS - Ferreira, J. P. [UNESP]; Andreotti, M. [UNESP]; Pascoaloto, I. M. [UNESP]; Costa, N. R. [UNESP]; Augusto, J. G. [UNESP] (Inst Zootecnia, 2018)
Because of the great emphasis on climate change in recent decades, the search for sustainable and balanced cropping systems has grown along with the search for soil conservation and reduced use of inorganic farm inputs. From this view, the research was to study the influence of different intercropping and succession in the physical and chemical attributes of a clayey Oxisol in the Cerrado conditions. The experimental design was randomized blocks with treatments: maize seeding spacing of 0.45 m or 0.90 m, intercropped with Xaraes grass or Tanzania grass, followed by fodder pasture maintenance in the area fertilized or not with 250 kg/ha N (split in 5 applications), and succeeded by soybeans. It was determined the chemical and physical soil attributes, mechanical resistance to penetration, gravimetric humidity and stock of carbon of the soil in four periods: before installing the consortia, after the maize harvest, after drying out the pastures and after soybean harvest. The plots with higher dry matter yield were those that resulted in an increase in organic matter content, soil stock of carbon and greater cycling of nutrients from deeper layers. There was no influence of corn spacing on the physical and chemical soil properties. The use of different species simultaneously in the area results in a reduction in the penetration resistance and increase of the porosity of the soil by differential growth of the roots.
Keywords: Glycine max; Integrated Crop-Livestock; Megathyrsus maximus; Urochloa brizantha; Zea mays